1984
DOI: 10.1128/iai.45.1.155-159.1984
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of fibroblast proliferation by oral spirochetes

Abstract: Soluble sonic extracts of several strains of Treponema denticola and Treponema vincentii were examined for their abilities to alter proliferation of both murine and human fibroblasts. We found that sonic extracts of all tested strains of T. denticola caused a dose-dependent inhibition of murine and human fibroblast proliferation when assessed by both DNA synthesis ([3H]thymidine incorporation) and direct cell counts. T. vincentii had only a minimal inhibitory effect at comparable doses. No inhibition was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
37
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 17 publications
2
37
0
Order By: Relevance
“…The polypeptide proteins detected on the outer envelopes of treponemes may contribute to adherence to specific or non-specific substrates present on host cells (5,6,9,25,26,33), tissue damage of hosts (3,22) or antibody production tn vivo (10,12,30). Recently we reported that 77 dentieota ATCC 33520 possessed several fibronectin-binding polypeptides, including 3 main polypeptides P9, PI 1 and P16, suggesting that fibronectin on host cells can mediate cytoadherence of this microorganism by its binding to the outer envelopes or the exposed axial flagella (31).…”
Section: Discussionmentioning
confidence: 99%
“…The polypeptide proteins detected on the outer envelopes of treponemes may contribute to adherence to specific or non-specific substrates present on host cells (5,6,9,25,26,33), tissue damage of hosts (3,22) or antibody production tn vivo (10,12,30). Recently we reported that 77 dentieota ATCC 33520 possessed several fibronectin-binding polypeptides, including 3 main polypeptides P9, PI 1 and P16, suggesting that fibronectin on host cells can mediate cytoadherence of this microorganism by its binding to the outer envelopes or the exposed axial flagella (31).…”
Section: Discussionmentioning
confidence: 99%
“…Small-sized spiroehetes are among the most frequently found bacteria in periodontal pockets and are among the suspected periodontal pathogens (14), as they produce tissue-destroying enzymes, such as trypsin and hyaluronidase, and cytotoxic metabolic products, such as indole and hydrogen sulfide (7,13). Furthermore, these bacteria are able to evade normal host responsiveness by inhibiting polymorphonuclear leukocyte functions and fibroblast proliferation (3,4).…”
mentioning
confidence: 99%
“…Treponema denticola, have shown that spirochetes may contribute to the inflammatory process, as these strains could ferment glucose and some amino acids to cytotoxic products (8,9). Furthermore, in recent studies it has been observed that spirochetes interact with some host cells in supressing fibroblast growth and inhibiting the function of neutrophil granulocytes (10)(11)(12). However, better cultivation methods are needed to gain further information about the pathogenic effect of spirochetes on periodontal disease.…”
mentioning
confidence: 99%